Plagiarism and Ethics for Medical and Scientific Researchers - Shitalkumar Sagari (Journal of Dental Problems and Solutions - Peertechz Publications, 2014)
It is the responsibility of educators at medical institutions and departments to teach their students about writing ethics and best practices. The principle of good medical writing or scientific writing is a clear, brief, exact, and it should be honest presentation of the scientific ideas.